A modern migration theory : an alternative economic approach to failed EU policy - Hansen, Peo (Comparative political economy., 2021)
How does the EU square the seemingly contradictory objectives of bringing about less migration - its current approach to the refugee crisis - and more migration, which is its current response to the Union's demographic deficit? Peo Hansen explores how this might be resolved.